2016
DOI: 10.17569/tojqi.79489
|View full text |Cite
|
Sign up to set email alerts
|

Öğretim Elemanlarının Yaşamboyu Öğrenmeye Yönelik Görüşleri

Abstract: ÖzBu çalışmanın amacı, öğretim elemanlarının yaşamboyu öğrenmeye yönelik düşüncelerini ve yaşamboyu öğrenme özelliklerini etkileyen faktörleri ortaya koymaktır. Bu amaç doğrultusunda söz konusu araştırma olgu bilim deseni ile desenlenmiştir. Araştırmanın

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Furthermore, negative attitude of colleagues is also one of the obstacles preventing lifelong learning. This conclusion is in line with the conclusions of studies carried out Haseski and Odabaşı (2016), İnandı, Tunç and Uslu (2013) and Stewart (2009). TTuzgöl-Dost and Cenkseven (2007) also revealed that the negative interpersonal relationships have also a negative influence on the attitudes of academics.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Furthermore, negative attitude of colleagues is also one of the obstacles preventing lifelong learning. This conclusion is in line with the conclusions of studies carried out Haseski and Odabaşı (2016), İnandı, Tunç and Uslu (2013) and Stewart (2009). TTuzgöl-Dost and Cenkseven (2007) also revealed that the negative interpersonal relationships have also a negative influence on the attitudes of academics.…”
Section: Discussionsupporting
confidence: 91%
“…In this study results clearly outlined that necessities such as lecture load and administrative duties, and responsibilities related to family life influence becoming lifelong learners negatively. Similarly, related literature point out lecture load and administrative duties (Haseski and Odabaşı, 2016;Clapper, 2010;Jivanjee, Pendell, Nissen and Goodluck, 2015;Çolakoğlu, 2005;Visakorpi, Stankovic, Pedrosa & Rozsnyai, 2007), and family responsibilities (Haseski and Odabaşı, 2016;Gouthro, 2005;Köle, 2011) are preventing individuals from lifelong learning. Furthermore, negative attitude of colleagues is also one of the obstacles preventing lifelong learning.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They found a high level of lifelong learning attitudes of professors and associate professors similar to the research data. Haseski and Odabaşı (2016), in their study to determine the factors affecting lifelong learning according to faculty members, determined that the academic titles of the academicians participating in the research increased in the scores obtained from the lifelong learning questionnaire as they progressed. It has also been found that there are studies in the literature that do not differ by researchers.…”
Section: Lifelong Learning Tendency and Thinking Style Levels Of Acad...mentioning
confidence: 99%